Analisis Kebijakan SE Dirjen Pendis No. 10 Tahun 2024 Panduan Program Makan Bergizi Gratis di Lingkungan Pesantren: Implikasi terhadap Motivasi Belajar Santri - Amiruddin Setiawan; Harti Purwanti; Hani Cahya Maulani; Fuzi Nurani Anggraeni; Muhammad Andriana Gaffar (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the Implementation of the Policy of the Directorate General of Islamic Education Circular No. 10 of 2024 concerning the Free Nutritious Meal Program (MBG) at the Tarogong Islamic Boarding School, Garut Regency, and its impact on students' learning motivation. Education, especially in Islamic boarding schools, requires special attention regarding adequate nutritional access for students, which has a significant impact on the learning process. The research method used is a qualitative approach with a case study design, which allows researchers to explore in depth the experiences and perceptions of students, teachers, Islamic boarding school leaders, kitchen managers and parents regarding this program. The results of the study indicate that this policy has a positive impact on students' learning motivation, where the majority of students reported increased enthusiasm and concentration in participating in learning after receiving nutritious food intake regularly. However, there are challenges in its implementation, such as the quality of distribution and the need for training for supporting staff. This study provides recommendations for related parties to improve collaboration between educational institutions, local governments, and logistics providers for the sustainability of the program, as well as implementing evaluation mechanisms to improve aspects that are less effective. In conclusion, the Free Nutritious Meal Program (MBG) not only functions as a nutritional intervention, but also as an important strategy in improving the motivation and learning achievement of students in Islamic boarding schools.